Pembuatan Web E-Commerce untuk Penjualan Baju Batik pada Toko Uunyil Klaten - Maratushsholihah, Aprilia; Ismudibyo, Ikrar Akmal; Cahyana (eProceedings of Applied Science, 2025)
Abstract— Batik is one of Indonesia's cultural heritages that has been recognized worldwide, and since 2009, batik has been designated by UNESCO as a Masterpiece of the Oral and Intangible Heritage of Humanity. However, many batik businesses still market their products conventionally, including Toko Unyil Klaten, which relies solely on physical stores and word-of-mouth promotion. The development of this application is crucial to expand market reach and enhance business competitiveness amid the growing trend of online shopping. According to data from the Central Statistics Agency, the value of e-commerce transactions in Indonesia continues to increase, indicating a shift in consumer behavior toward online shopping. Therefore, the development of an e-commerce web application is a strategic solution to help SMEs like Toko Unyil expand their market, improve operational efficiency, and strengthen their competitiveness. The development method used is the waterfall approach, starting from the requirements analysis stage, interface design, implementation, to functional testing. The tools used in the development include the Laravel framework as the main PHPbased framework, MySQL as the database management system, Visual Studio Code as the code editor, and GitHub as the collaboration and version control platform. Testing results indicate that all features function properly according to user needs, both from the admin and buyer perspectives. With the launch of this e-commerce web application, Toko Unyil Klaten is expected to improve operational efficiency, reach a broader consumer base, and strengthen its presence in the increasingly competitive digital batik market. Keywords— batik, digital promotion, e-commerce, Laravel, MSME (Micro, Small, and Medium Enterprise), website